United Kingdom-Hong Kong : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1997)
This Selected Issues paper reviews the key institutions and arrangements for economic policymaking that were expected to be put in place following the transfer of sovereignty over Hong Kong to China in 1997. International treaties between Britain and China from the nineteenth century are reviewed. The paper discusses Hong Kong's current and future constitutional documents-the Letters Patent and Royal Instructions, and the Basic Law, respectively. The paper also provides a background on the system of government in Hong Kong in 1997.